Degradation of Troponin I in Serum or Plasma: Mechanisms, and Analytical and Clinical Implications - Lippi, Giuseppe; Cervellin, Gianfranco (Seminars in Thrombosis and Hemostasis, 2012)
A prolonged myocardial ischemia, which results from a total deprivation of blood supply to an area of cardiac muscle for an appreciable period of time, is the leading mechanism responsible for acute myocardial infarction (AMI). The irreversible injury of myocardiocytes and the subsequent release of a variety of intracellular components into blood is the cornerstone of the diagnosis of AMI. Cardiac troponins are advocated as the biochemical gold standards among the various biomarkers of plaque instability, plaque rupture, ischemia, reversible cellular injury, and early and late necrosis (i.e., irreversible injury). The assessment of cardiac troponins in the diagnostic approach of patients with chest pain presents, however, some specific challenges due to the complex mechanisms of release from the injured myocardium, as well as to the enzymatic degradation by cardiac and extracardiac proteases (i.e., calpains, caspases, cathepsin L, and gelatinase A) that might alter the immunoreactivity (and thus laboratory detection) of the molecules. These two aspects will be discussed in this article, with specific focus on cardiac troponin I, as a variety of immunoassays based on antibodies which recognize different epitopes on the molecule is available for the measurement of this important cardiac biomarker.
Keywords: troponin; proteolysis; degradation; interference; preanalytical variability